Sistem Informasi Akademik Berbasis Web pada Lembaga Bimbingan Belajar - Dwi Novia Prasetyanti; Antonius Agung Hartono; Agung Tri Laksono (Journal of Innovation Information Technology and Application (JINITA), 2020)
The Cendika Cilacap Tutoring Institute is a learning institution that provides learning programs for elementary, junior high and high school students. In Cendika Cilacap, academic data management is still done by means of books and has not been computerized, such as student registration data, delivery of value information, delivery of schedule information, and reports to leaders are still done manually. The problem that arises is that the increasing number of academic data, so there must be a system that can accommodate these data properly and can improve services. This study aims to develop a Web-based academic information system that can assist in managing academic data, student registration process, delivery of value information, delivery of schedule information and reports to leaders. This application was developed with the waterfall method. Based on the results of questionnaire testing with 10 respondents, it was enough for 4%, both 32%, and very good at 64%, that this application can help and make it easier to manage academic data and solve problems that occur in Cilacap cendika.